2007
DOI: 10.1080/00016350701678725
|View full text |Cite
|
Sign up to set email alerts
|

Effects of estrogen deficiency on tooth movement after force application: an experimental study in ovariectomized rats

Abstract: Estrogen deficiency increased orthodontic tooth movements but counts of osteoblasts, which are responsible for new bone formation, were lower in regions of tension and of pressure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(40 citation statements)
references
References 17 publications
0
40
0
Order By: Relevance
“…Arslan et al . observed an increase in the number of osteoclasts in the periodontal tissue during accelerated OTM in OVX rats 17 . Tan et al .…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…Arslan et al . observed an increase in the number of osteoclasts in the periodontal tissue during accelerated OTM in OVX rats 17 . Tan et al .…”
Section: Introductionmentioning
confidence: 86%
“…It has been reported that estrogen deficiency accelerates OTM in OVX rats 2, 5, 1720 . Arslan et al .…”
Section: Introductionmentioning
confidence: 98%
“…The impressions (Express TM STD, 3M ESPE, U.S.A.) of the upper jaw of all animals were taken with an individual acrylic impression tray on the 1 st day of the experiment. The previous studies have used the incisors in rats as an experimental model for exploring the effect of pharmaco-therapeutic agents on orthodontic tooth movement [13,14]. After the impression had been taken, an elastic band (elastic separator Ø 1.5 mm Dentalastics  Separators, Dentaurum, Germany) was inserted between the incisors.…”
Section: Samplesmentioning
confidence: 99%
“…The upper jaws were dissected and the separation of the right and left maxilla was performed with a diamond separator (Diamantscheibe 30 mm Ø, Bredent, Germany). The same region was excised in all rats, along the upper left central incisor root toward the apex of the alveolar bone on the mesial and distal sides, 3 mm above the apex towards the crown, as per previously described method [13].…”
Section: Histological Examinationmentioning
confidence: 99%
“…[ 8 9 ] Therefore, orthodontists need to be aware of any possible chronic medical conditions that might interfere with overall success of orthodontic treatments. To date, various systematic factors such as different hormonal changes including hyperparathyroidism,[ 10 ] hyper and hypothyroidism,[ 11 12 ] calcium-deficient,[ 13 ] and ovariectomization[ 14 15 16 ] have also been implicated as potential risk factors to individualize the prediction of each patient's risk of developing EARR, but the result remains controversial.…”
Section: Introductionmentioning
confidence: 99%